One pot oxidative ethyl acetate synthesis using palladium activated SBA-15 type catalysts - Yesim Gucbilmez; Ibrahim Calis (Heliyon)
Ethyl acetate, an important fuel additive and green solvent, was produced through one pot oxidative synthesis of EtOH using palladium incorporated SBA-15 type catalysts synthesized by the impregnation (IMP) method. This was the first time these catalysts were used in this reaction at mild EtOH vaporization conditions (35 °C). XRD, N2 physisorption, SEM, CO chemisorption and TPR methods were used to characterize the as-synthesized catalysts. All the catalysts were found to maintain the SBA-15 semi-crystalline structure with high BET surface areas (626–665 m2/g), and high pore volumes (0.93–0.95 cm3/g) and metal distributions in the range of 24–29 %. The optimum Pd/Si molar ratio in solution was found to be 0.03 and the corresponding catalyst was tested in the one pot oxidative synthesis of ethyl acetate at different reaction temperatures and different O2/EtOH molar ratios. The maximum ethyl acetate yield was obtained as 0.25 at 200 °C and 1 atm at an O2/EtOH molar ratio of 0.5 and space velocity of 2206 h−1 using this catalyst. The fact that the best yield was obtained at mild conditions of temperature and pressure decreased the energy requirement of the ethyl acetate production process. In addition, in Turkey, bio-ethanol is produced from sugar beet pulp, thus, the oxidative synthesis of ethyl acetate can be made more sustainable by using sugar beet based ethanol.